Cultural Perception of Ghost in KKN Desa Penari Movie - Aulia Ikhtiar Tamami (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This study aims to analyze how culture affects individual perceptions of ghost phenomena encountered in everyday life. This movie is in the spotlight because it combines horror elements with local cultural elements that can affect how the audience understands and interprets ghosts in their cultural context. The method used in this research is qualitative analysis. The data collected includes documentation. Data analysis was conducted by identifying common themes that emerged in the audience's perception of ghosts in the KKN Desa Penari film. The results of this study can provide an overview of how ghosts in this film affect the cultural perceptions of its audience.